Minimally Invasive Mitral Valve Surgery Utilizing Heart Port Technology. Issue 3 (4th February 2014) - Vallabhajosyula, Prashanth; Wallen, Tyler J.; Solometo, Lauren P.; Fox, Jeanne; Vernick, William J.; Hargrove, W. Clark
Abstract Objective To determine operative outcomes of right mini‐thoracotomy mitral valve surgery utilizing port access technology in first‐time and reoperative cardiac surgery patients. Methods From 2002 to 2011, 881 patients underwent minimally invasive mitral valve surgery. Of these, 154 patients had previous cardiac operations via sternotomy (Group 1), of which 18 (12%) had two previous operations. Seven hundred and twenty‐seven patients had no previous cardiac operations (Group 2). Results Patient demographics were similar in both groups. In Group 1, 76 (49%) patients had previous coronary artery bypass grafting, 13 (8%) had previous aortic valve surgery, and 57 (37%) had previous mitral valve surgery. Preoperative echo findings for Groups 1 and 2 included severe mitral regurgitation (MR) (88%, n = 135; 94%, n = 687), mitral stenosis (MS) (4%, n = 6; 2%, n = 12), MS + MR (8%, n = 13; 4%, n = 28), and ejection fraction (48%, 56%). Operative procedures in Groups 1 and 2 were MV repair (54%, n = 84; 89%, n = 645) and MV replacement (46%, n = 70; 11%, n = 82). Circulatory management techniques for Groups 1 and 2 included endoballoon (75%, n = 116; 79%, n = 576), Chitwood clamp (8%, n = 12; 20%, n = 147), and fibrillatory arrest (17%, n = 30; 0.5%, n = 4). Perioperative outcomes were: stroke: 2.5%, 1.6%; reoperation for bleeding: 5%, 6%; valvular reoperation rate: 0.6%, 2%; aortic dissection: 2.5%, 1%; and wound infection: 0%, 0%. Transfusion requirement was 49% (n = 76) and 31% (n = 232), respectively. Median hospital stay was seven and seven days, respectively. On postoperative echocardiography, 98% (n = 151) and 99% (n = 718) of patients had zero or trace MR (1+) with 100% freedom from MR > 2+. In‐hospital mortality was 3% (n = 5) and 1% (n = 8). Conclusions Operative outcomes with minimally invasive mitral valve surgery utilizing port access technology can be performed safely. Stroke rate was higher in the reoperative cases (p = NS) although similar to reports evaluating redo sternotomy in mitral valve cases. doi: 10.1111/jocs.12293 (J Card Surg 2014;29:343–348)